2009
DOI: 10.1007/s11999-009-0765-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Conflicting Meta-Analyses in Orthopaedic Surgery

Abstract: Meta-analyses are important evaluations in orthopaedic surgery, not only to create clinical guidelines, but also because their findings are included in public health and health policy decision making. However, with increasing numbers of meta-analyses, discordant and frankly conflicting conclusions have been reported. We searched for conflicting meta-analyses, ie, those arriving at different conclusions despite following the same research question, identified potential reasons for these differences, and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
(65 reference statements)
0
30
0
Order By: Relevance
“…To pool data, we used a random effects model to control for increased study heterogeneity. The more conservative random effects model involves an assumption that the effects being estimated in the different studies follow some distribution, but results in wider confidence intervals [11,44,45].…”
Section: Methodsmentioning
confidence: 99%
“…To pool data, we used a random effects model to control for increased study heterogeneity. The more conservative random effects model involves an assumption that the effects being estimated in the different studies follow some distribution, but results in wider confidence intervals [11,44,45].…”
Section: Methodsmentioning
confidence: 99%
“…Few other studies, mainly anecdotic, have investigated sources of discordance among SRs: different interpretation of identical quantitative results [8]; different interpretation due to noncomparable analyses because of, mainly unmotivated, subgroup analyses; different selection of primary or secondary outcomes [6]; different inclusion criteria [6]; and different meta-analytical approaches [9,28]. Our systematic attempt to explore the theoretical model proposed by Jadad et al [5], although limited to the cardiologic field, confirms many of the sources of discordance hypothesized.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Biomechanical evaluations have demonstrated that differences do exist between the two autografts but they have not reached a consensus regarding the superiority of one autograft over the other in restoring neuromuscular function at the knee joint [10,12,13]. This is most evident in systematic reviews that have conflicting results as each favour one or the other graft [14]. It is possible that the examination of gait variability could better elucidate which autograft (BPTB or ST/G) is more suitable for ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%